2008
DOI: 10.1002/prot.22081
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of virtual lead optimization: The role of the receptor structure and ensembles in accurate docking

Abstract: Accurate ranking during in silico lead optimization is critical to drive the generation of new ligands with higher affinity, yet it is especially difficult because of the subtle changes between analogs. In order to assess the role of the structure of the receptor in delivering accurate lead ranking results, we docked a set of forty related inhibitors to structures of one species of dihydrofolate reductase (DHFR) derived from crystallographic, NMR solution data, and homology models. In this study, the crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…It has already been reported previously that use of multiple receptor conformation improves the virtual screening performance if receptor ensemble is chosen carefully among the available crystal structures or molecular dynamics generated conformers [50,51]. We observed that if top five receptors that performed best in single receptor docking are chosen, the AUC value goes up.…”
Section: Retrospective Analysis Of Sampl3 Challenge Resultssupporting
confidence: 45%
“…It has already been reported previously that use of multiple receptor conformation improves the virtual screening performance if receptor ensemble is chosen carefully among the available crystal structures or molecular dynamics generated conformers [50,51]. We observed that if top five receptors that performed best in single receptor docking are chosen, the AUC value goes up.…”
Section: Retrospective Analysis Of Sampl3 Challenge Resultssupporting
confidence: 45%
“…This may be largely due to the fortunate result of relatively minor induced-fit adaptations of proteins upon ligand binding. [27] It is surprising that homology models often provide significant enrichment of actives against a background of decoys. A variety of successful VS studies based [19,[28][29][30] In a retrospective study, Gilson and co-workers [31] analyzed five drug targets for which the crystal structure was available.…”
Section: Discussionmentioning
confidence: 99%
“…The "right' conformations should be able to provide the best results in terms of quantity and quality, where quantity corresponds to the percentage of active molecules identified in the early screening stage, and quality to the chemical diversity of these first ranked molecules. Both single-and multiple receptor conformation approaches [24] are significantly affected by the chosen binding site architecture, so that the key point is often represented by the capability of the conformational sampling to select the most representative states [145,190]. Some strategies were recently proposed to guide this conformational sampling.…”
Section: Choosing the Right Receptor Conformation In Virtual Screeningmentioning
confidence: 99%
“…In silico methodologies able to deal implicitly or explicitly with protein flexibility in drug design include soft docking [135,136], docking with libraries of side-chain rotamers [136], algorithms accounting for induced-fit adjustments [70,137], Monte Carlo sampling [62,138] and MD simulations [139]. More recently docking into multiple conformations coming from X-ray [140][141][142], NMR [143,144], a combination of both [145,146] or computationally generated by MD simulations [147,148], normal-mode analysis [63,66,149], Monte Carlo [62,150], or homology models [83] have been successfully applied.…”
Section: The Ligand Binding Event: Old and New Perspectivesmentioning
confidence: 99%